2011
DOI: 10.1074/jbc.m110.156430
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum Stress Sensor, ATF6α, Protects against Neurotoxin-induced Dopaminergic Neuronal Death

Abstract: Oxidative stress and endoplasmic reticulum (ER) stress are thought to contribute to the pathogenesis of various neurodegenerative diseases including Parkinson disease (PD), however, the relationship between these stresses remains unclear. ATF6␣ is an ER-membrane-bound transcription factor that is activated by protein misfolding in the ER and functions as a critical regulator of ER quality control proteins in mammalian cells. The goal of this study was to explore the cause-effect relationship between oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 35 publications
6
77
2
Order By: Relevance
“…It has been reported by Silva et al [115], that deficiency of CHOP, a key ER stress marker, protects the neonatal striatum from neurotoxicant 6-hydroxydopamine. Reports also showed that forced expression of ER stress sensor proteins, ATF6 alpha [117] and spliced XBP1 [116], confines neurotoxininduced dopaminergic neuronal death [117]. These reports are indicative of the role of ER stress in the death and dysfunction of dopaminergic neurons exposed to neurotoxicant models of PD.…”
Section: Er Stress and Parkinson's Diseasementioning
confidence: 83%
“…It has been reported by Silva et al [115], that deficiency of CHOP, a key ER stress marker, protects the neonatal striatum from neurotoxicant 6-hydroxydopamine. Reports also showed that forced expression of ER stress sensor proteins, ATF6 alpha [117] and spliced XBP1 [116], confines neurotoxininduced dopaminergic neuronal death [117]. These reports are indicative of the role of ER stress in the death and dysfunction of dopaminergic neurons exposed to neurotoxicant models of PD.…”
Section: Er Stress and Parkinson's Diseasementioning
confidence: 83%
“…9) In addition, drugs which induce PD, such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), cause ER stress, and the involvement of ATF6 activation in this process has been reported. 31) While nitric oxide (NO) is known to induce ER stress, protein-disulfide isomerase (PDI) that works on protein disulfide bond formation in the ER has been identified as a NO target. When cysteine residues in the PDI enzyme active sites are Snitrosylated by NO, the enzyme activity declines, resulting in the accumulation of defective proteins in the ER.…”
Section: Er-associated Degradation (Erad)mentioning
confidence: 99%
“…This observation was also confirmed in a model where XBP1 is delivered to neuronal stem cells transferred to animals treated with rotenone [90]. ATF6 deficient animals exhibit increased ubiquitin positive inclusions and exacerbated dopaminergic neuron loss following MPTP treatment [91,92]. Overexpression of BiP using a gene therapy strategy also proved to be neuroprotective for dopaminergic neurons after overexpression of human α-synuclein in rats [93].…”
Section: Parkinson's Diseasementioning
confidence: 58%